PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP TAX ADVOIDANCE - Agustin, Pingki; Husin, Ahmad; Ngaisah (JURNAL ILMIAH EDUNOMIKA, 2025)
Tax avoidance has become a common case in Indonesia, as done by PT. Indofood Sukses Makmur Tbk, PT Andaro, and British American Tobacco (BAT) companies. The aims of this research is to determine the implication of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on Tax Avoidance. The study was conducted using a descriptive method. The results of the study concluded that corporate social responsibility has an implication on tax advoidance in consumer non-cyclicals even basic materials sector companies listed on the IDX for the 2021-2023. In this case, corporate social responsibility has the greatest influence among other variables on tax advoidance. Other variables include institutional leadership and board of commissioners, where institutional ownership has no implication on tax advoidance in consumer non-cyclical and basic materials sector instation listed on the IDX for the 2021-2023, while an independent board of commissioners has no implication on tax advoidance in consumer non-cyclical even basic materials sector instantion listed on the IDX for the 2021-2023.